Interannual Variability of Yellowfin Tuna (Thunnus albacares) and Bigeye Tuna (Thunnus obesus) Catches in the Southwestern Tropical Indian Ocean and Its Relationship to Climate Variability - Kim, Jihwan; Na, Hanna (Frontiers in Marine Science, 2022)
This study investigated the interannual variability of yellowfin tuna (Thunnus albacares) and bigeye tuna (Thunnus obesus) catches in the southwestern tropical Indian Ocean (SWTIO) over 25 years and its relationship to climate variability. The results indicate that the catch amount in the northern SWTIO exhibits a significant relationship with the temperature, salinity, and current variability in the upper ocean (< 400 m), associated with a significant subsurface upwelling variability, which is prominent only in the northern region. An increase of the tuna catches in the northern region is associated with the deepening of the thermocline depth and 20°C isotherm depth of the Seychelles–Chagos Thermocline Ridge, indicating suppression of the subsurface upwelling. Further analysis reveals that the catch amounts in the SWTIO tend to increase during the positive phase of the Indian Ocean Dipole. However, the catch variability in the northern SWTIO is more closely related to the El Niño–Southern Oscillation than the Indian Ocean Dipole. Favorable conditions for catches seem to develop in the northern region during El Niño years and continue throughout the following years. This relationship suggests the potential predictability of catch amounts in the northern SWTIO, an energetic region with strong subsurface upwelling variability.